Evaluasi Dan Pemodelan Proses Bisnis Registrasi Akademik Dengan Pendekatan Quality Evaluation Framework (Studi Kasus: Politeknik Unisma) - Topan Prakoso; Aditya Rachmadi; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Polytechnic UNISMA is a private entity engaged in education in Malang. In performing their duties there are certain areas that handle certain tasks such as academic field at Polytechnic UNISMA. In academic there are three main business processes that run such as the scheduling of courses, the process of making KRS and the process of making KHS. In conducting the current business process there are some activities that are not in accordance with the target given, therefore it will affect the performance of Polytechnic UNISMA. So we need to evaluate the current business process using Quality Evaluation Framework (QEF) to find out the gap that occurs between calculation with QEF and target. Where to do first is modeling business processes using Business Process Model and Notation (BPMN). The second determines the Quality Factor for several activities that run, then done the calculation on Quality Factor is with Quality metric and identified on Quality Factor that is not in accordance with the target Polytechnic UNISMA. Where identification using Root Cause Analysis to find the root of the problem on the Quality Factor. The result is to find out why a gap exists and root of the problem on the Quality Factor.